Manipulation of Time- and Frequency-Domain Dynamics by Magnon-Magnon Coupling in Synthetic Antiferromagnets - Xing Chen; Cuixiu Zheng; Sai Zhou; Yaowen Liu; Zongzhi Zhang (Magnetochemistry, 2021)
Magnons (the quanta of spin waves) could be used to encode information in beyond Moore computing applications. In this study, the magnon coupling between acoustic mode and optic mode in synthetic antiferromagnets (SAFs) is investigated by micromagnetic simulations. For a symmetrical SAF system, the time-evolution magnetizations of the two ferromagnetic layers oscillate in-phase at the acoustic mode and out-of-phase at the optic mode, showing an obvious crossing point in their antiferromagnetic resonance spectra. However, the symmetry breaking in an asymmetrical SAF system by the thickness difference, can induce an anti-crossing gap between the two frequency branches of resonance modes and thereby a strong magnon-magnon coupling appears between the resonance modes. The magnon coupling induced a hybridized resonance mode and its phase difference varies with the coupling strength. The maximum coupling occurs at the bias magnetic field at which the two ferromagnetic layers oscillate with a 90° phase difference. Besides, we show how the resonance modes in SAFs change from the in-phase state to the out-of-phase state by slightly tuning the magnon-magnon coupling strength. Our work provides a clear physical picture for the understanding of magnon-magnon coupling in a SAF system and may provide an opportunity to handle the magnon interaction in synthetic antiferromagnetic spintronics.